Le contrôle de la discrimination raciale au Canada - Tarnopolsky, Walter (Les Cahiers de droit, 1977)
This article is divided into four parts: the first is a brief survey of race relations in Canada before the enactment of anti-discrimination legislation; the next two parts are devoted to an outline of the scope of this legislation and of the administration and enforcement of it ; finally, the last part suggests some current and possible future developments to make it more effective. Prior to the nineteenth century both the French and the British settlers in the colonies that have become a part of Canada had slaves. Slavery was not, however, very extensive due to lack of large agricultural holdings. At the end of the eighteenth century the legislature in Upper Canada and some judges in Lower Canada limited its expansion and helped to end its practice. The British Imperial Emancipation Act of 1833 brought it to an end. In the next few decades, up to the American Civil War, some Canadians helped run-away slaves from the slave-holding states in the United States, while others actively discouraged them from coming. By the end of the nineteenth century a new source of racial tension arose on the West Coast between the newer immigrants from Asia and the older immigrants from Europe. The result was the enactment of numerous discriminatory laws by the legislature of British Columbia and subsequently, on a lesser scale, by the other western provinces. Most of these remained on the statute books until after World War II. None of these laws were held invalid by the courts on the basis of their discriminatory nature. In addition, both the common law and the Civil Code were interpreted as not prohibiting private discrimination, except by hotel-keepers and common carriers. The change from this situation started in the I930's with a few specific legislative prohibitions of discrimination in specific instances. In the 1940's Ontario, with respect to signs and advertisements and Saskatchewan, with respect to a whole range of activities, enacted legislation prohibiting discrimination, enforcing their prohibitions with penal sanctions. The 1950's saw the introduction of fair employment and fair accommodation practices acts. By the I960's these were being consolidated into comprehensive human rights codes administered by human rights commissions. This trend has continued up to this year, with the result that all eleven jurisdictions have commissions charged with enforcing antidiscrimination codes or acts. The usual, but not invariable, procedure is the laying of a complaint, the investigation of it by the commission staff, an attempt to bring about a settlement and finally, failing that, a hearing before an adjudicative tribunal to determine whether an act of discrimination did occur and, if so, what redress is appropriate. In concluding, three suggestions are made regarding measures that could be taken to strengthen the effectiveness of anti-discrimination legislation: (I) contract compliance; (2) greater independence for the commissions from the government; and (3) giving the legislation paramountcy over other statutes.